2020
DOI: 10.37394/232013.2020.15.5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Composite Inclined Weir – Gate Hydraulic Structure

Abstract: Composite hydraulic structure is widely used in irrigation system which consists of two parts. The first part is responsible for overflow regime and is represented by a weir, whereas the second part is responsible for underflow regime and is represented by a gate. Both elements play significant role to control, measured, and divert the flow. So it dominates the hydraulic regimes of open channel or river with high responsibility and accuracy. The target of this study is to investigate the effect of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The volume method is used to measure the actual discharge while a scale point gauge is used to measure the water depth. Weir -gate device (hydraulic structure) models are manufactured from wood sheet with thickness 5 mm beveled along all the edges at (45°) and with sharp edges of thickness (1 mm) [13]. The baffles are manufactured by wood with 5 mm thickness.…”
Section: Engineeringmentioning
confidence: 99%
“…The volume method is used to measure the actual discharge while a scale point gauge is used to measure the water depth. Weir -gate device (hydraulic structure) models are manufactured from wood sheet with thickness 5 mm beveled along all the edges at (45°) and with sharp edges of thickness (1 mm) [13]. The baffles are manufactured by wood with 5 mm thickness.…”
Section: Engineeringmentioning
confidence: 99%
“…From the results they found that the obstacles have a major impact on the hydraulic characteristics of the discharge structure like actual discharge, discharge coefficient, downstream water flow velocity, and downstream water depth. Qasim et al [4] did some experiments to assess the role of the combined discharge structure inclination angle in the alteration of the hydraulic structure characteristics. The inclination angle refers to the angle between the combined hydraulic structure and the horizontal bed of the flume.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have dealt with the issue of the weir-gate hydraulic structure. Qasim et al [1] did an experimental study to assess the influence of weir-gate hydraulic structure inclination angle, the study adopted angle range from 45 degrees to 135 degrees with the horizontal bed of the flume and compared the result with the case when the inclination angle equal to 90 degrees. The investigations include the impact of the inclination angle on the actual flow rate, discharge coefficient, water depth at the downstream region of the flume, and cross-sectional area of flow which crosses the gate and weir respectively.…”
Section: Introductionmentioning
confidence: 99%